Hypothetical Learning Trajectory (HLT) for Fraction of Blind Students Using Braille Media Fraction Block - Riza Agustiani; Agustiany Dumeva Putri (Didaktik Matematika, 2021)
Fraction is one of the difficult topics for students with visual impairments. Therefore, it is necessary to develop a learning trajectory that can help the students understand fractions. Thisdesign researchaims to describe the design process of hypothetical learning trajectory for the addition of fractions usingbraillefraction blocks. This research is divided into three stages: the preparation for the experiment (design), the implementation of the teaching experiment, and the retrospective analysis.Data collection techniques employed in this research were walkthrough, observation, interview, and test.The product of this research is hypothetical learning trajectory (HLT) for the addition of fractions that contains the following activities:comparing unit block and fraction blocks, comparing the size of different fraction blocks to get the same size fraction blocks (equal fraction), comparing the sizes of two fraction blocks, adding fraction blocks, and determining the fraction block with the same size as the added fraction block.Those five activities were carried out in the two-cycle experimental activities. After the implementation of the activities, the students' answers to exercises showed that the research subjects could add fractions, either with the same denominators ordifferentdenominators.